Irish-language sean-nós song as a resource in sociolinguistic research - Foran, James (Studia Celtica Posnaniensia, 2025)
This paper examines the potential role of Irish-language sean-nós song and its surrounding discourse in current areas of sociolinguistics, such as the idealisation of native speaker linguistic output, parallel conceptualisations of authenticity, and accent perception in relation to language attitudes and ideologies. Whilst much research continues to be carried out uncovering attitudes and speakers’ positioning within Irish-language contexts, explicit examination of these phenomena in the context of singing culture remains under-researched. In an extra-linguistic context, such research may provide additional insights or alternate perspectives on these sociolinguistic issues, whilst simultaneously developing approaches to sociolinguistic research that preserve language’s interrelation with the culture and cultural artefacts of the communities in which it is employed. Concurrently, research on accent perception in the context of song is limited and given the phonological breadth of Irish itself and its variation within dialects, regional accents, and pronunciation, this paper will also consider the possibility of sean-nós as a resource from which to further study accent recognition and perception beyond a strictly spoken context. By surveying relevant literature and highlighting parallels between these areas, this paper hopes to draw attention to the value of sean-nós and traditional song in multiple research focuses in sociolinguistics. Furthermore, the role of song in heritage and endangered language research has been highlighted as an area in need of further study in recent literature (e.g. Echeverria and Sparling 2024). Since Irish is a focus of revitalisation efforts, this paper also aims in a broader view to contribute to considerations of the potential value of song as a linguistic medium in revitalisation and cultural and linguistic transmission.